2015
DOI: 10.1007/s00294-015-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles of extracellular DNA in bacterial physiology

Abstract: In textbooks, DNA is generally defined as the universal storage material for genetic information in all branches of life. Beyond this important intracellular role, DNA can also be present outside of living cells and is an abundant biopolymer in aquatic and terrestrial ecosystems. The origin of extracellular DNA in such ecological niches is diverse: it can be actively secreted or released by prokaryotic and eukaryotic cells by means of autolysis, apoptosis, necrosis, bacterial secretion systems or found in asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 121 publications
1
80
1
2
Order By: Relevance
“…In addition to the role of secreted DNA in the transfer of genetic information, other roles, such as acting as a nutrient source or as an important structural component of biofilms have been suggested (For review see: Vorkapic et al 2016). At the onset of biofilm formation, the initially planktonic bacteria attach reversibly to the surface and start to produce an extracellular matrix of polymeric substances, which results in their irreversible attachment to the surface (Dunne 2002).…”
Section: Secreted Dna Affects Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the role of secreted DNA in the transfer of genetic information, other roles, such as acting as a nutrient source or as an important structural component of biofilms have been suggested (For review see: Vorkapic et al 2016). At the onset of biofilm formation, the initially planktonic bacteria attach reversibly to the surface and start to produce an extracellular matrix of polymeric substances, which results in their irreversible attachment to the surface (Dunne 2002).…”
Section: Secreted Dna Affects Biofilm Formationmentioning
confidence: 99%
“…These polymeric substances can consist of exopolysaccharides, secreted proteins, membrane vesicles or extracellular DNA. For many bacteria, including N. gonorrhoeae , it was demonstrated that extracellular DNA is an important component of the biofilm (Steichen et al 2011; Zweig et al 2014; Vorkapic et al 2016). Growth of N. gonorrhoeae MS11 biofilms in a medium containing Exonuclease I, which specifically degrades ssDNA, delayed biofilm formation in its initial phases (Zweig et al 2014).…”
Section: Secreted Dna Affects Biofilm Formationmentioning
confidence: 99%
“…More specifically, why does evolution favor and preserve a trait that is energy intensive and at the expense of the life of some cells within a pneumococcus population (by allolysis) but does not show immediate advantages? Indeed, despite its contribution to horizontal gene transfer (Vorkapic et al 2015), genetic transformation in itself has been shown to be dispensable for infection, as proven by the lack of virulence loss after deletion of genes essential for DNA uptake and recombination (Zhu et al , 2015. Excitingly, the first evidence which directly supports the X-state-for-fitness model was shown by our recently published study that distinguishes between competence-dependent 'late' genes that contribute to pneumococcal fitness versus those that are competence-independent (Zhu et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The DNA molecule has been previously described as a nutrient source, for recombination into the chromosome, for repair of the cell’s own DNA or as a building element in bacterial biofilms (Vorkapic et al, 2016). Nevertheless, theses physiological roles are attributed to DNA molecules found outside of the cell, also known as extracellular DNA (eDNA).…”
Section: Introductionmentioning
confidence: 99%